Remote Sensing in Mangroves II - Giri, Chandra (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Mangrove forests are in constant flux due to both natural and anthropogenic forces. The changing mangroves will have significant consequences to coastal communities. Observation and monitoring of the distribution and dynamics of mangroves is central to a wide range of scientific investigations conducted in both terrestrial and marine ecosystems. Recent advancements in remote sensing data availability, image-processing methodologies, computing and information technology, and human resource development have provided an opportunity to observe and monitor mangroves from local to global scales on a regular basis. The spectral, spatial, and temporal resolution of remote sensing data and their availability have improved, making it possible to observe and monitor mangroves with unprecedented spatial thematic and temporal details. This journal Remote Sensing Special Issue reprint dedicated to the observation and monitoring of mangroves using remote sensing from local to global scales. The Issue broadly covers the application of remote sensing using optical (multi-spectral and hyperspectral), radar, and Lidar data obtained from multiple platforms including ground, air, and space. The research papers published use the latest techniques to acquire, manage, exploit, process, and analyze a wide variety of remote sensing data for mangrove forest applications. Both research papers and innovative review papers are included.